The Role of Foreign Investors in Commercial Bank Stock Prices: Macroeconomic Factors & Internal Factors of the Company Moderated Net Foreign Investor Funds - Putra Chandra Wijaya (Dinasti Publisher, 2025)
This study aims to analyze the influence of macroeconomic factors and internal factors of the company on the share price of commercial banks in Indonesia, with the role of net foreign investor funds as a moderation variable. The macroeconomic variables studied include economic growth (G), inflation (INF), and exchange rate (Exchange Rate), while the company's internal variables include net interest margin (NIM), debt to equity ratio (DER), and loan to deposit ratio (LDR). This study uses quarterly time series data from 2018 quarter I to 2024 quarter IV with a research sample of 14 commercial banks consisting of 4 banks in the KBMI category 4 and 10 banks in the KBMI category 3 and uses panel data regression analysis with an interaction approach to test the effect of moderation of net foreign investor funds on the relationship between independent variables and stock prices. The findings of the study show that macroeconomic factors such as economic growth (G), inflation (INF), and the Rupiah exchange rate (KURS) as well as internal factors such as net interest margin (NIM) have a significant effect on the share price of commercial banks. Meanwhile, net foreign investor funds (NF) were proven not to moderate the relationship between macroeconomic factors and internal company factors to bank share prices. These findings suggest that the direct influence of foreign investors on the dynamics of bank stock prices may not be as strong as the independent variables of macroeconomic factors and internal factors of the company, so the direction of stock movements is more influenced by fundamental and macroeconomic conditions than net foreign investment funds.